Bi-directional LSTM-GRU Based Time Series Forecasting Approach - He, Bo; Li, Longbing; Bo, Yunya; Zhou, Jingxuan (International Journal of Computer Science and Information Technology, 2024)
Time series prediction is a basic regression task in data mining, and the research of traditional methods, machine learning and deep learning has made great progress in this area. In this paper, starting from the concept of long time series, feature extraction and other related techniques and data series prediction methods, we introduce the current research status of deep learning networks in time series data and analyze the application of deep learning networks in time series prediction.